Building the Students' English Vocabulary for Tourism through Computer-Based Corpus Approach - Andi Rizki Fauzi; S. Suradi (Indonesian Journal of Integrated English Language Teaching, 2018)
The use of computer as one of the technological advancement products  gives many benefits in the process of teaching and learning and there is no doubt of its contribution in learning English language. However, the use of Computer-Based Corpus Approach is not yet widely used in teaching English in higher education level especially in tourism major. Mostly, the teachers only focus on the use of source books and dictionary when they are teaching. That is why the students only learn limited vocabulary with little expossures and the vocabulary is learnt in isolation as the students attempt to get the meaning of  certain word list from the dictionary. Therefore, the purpose of this research was to investigate whether the students who were taught by using Computer-Based Corpus Approach could build their English vocabulary for tourism  better than  those who were taught without Computer-Based Corpus Approach. This research was an experimental research. The population of the research was all the  fouths semester students from Diploma III majoring in Hospitality consisting of 151 students and they were divided into 5 classes in which class A and B have chosen as the samples. However, the stuedents who administered pre-test were 56 students and when the post-test was held the students who attended the tes were only 53 students. After Computer-corpus Based approach was carried out in the experimental class, this did not have a  significant difference assisting the students building their English vocabulary for Tourism than those who did not employ it. It can be seen from the result of independent sample t-test which showed that Sig. (2-tailed) score was 0,431 which is more than 0,05 meaning that Ho was rejected. This approach was considered  time consuming and required big effort to understand the corpus data due to many unfamiliar words in the real texts found. However, overall the students had positive attitude with this approach.